Analisis Faktor Yang Berpengaruh Terhadap Pendapatan Asli Daerah di Kalimantan Utara - Rantika, Jihni; Boedirochminarni, Arfida (Jurnal Ilmu Ekonomi JIE, 2023)
This study aims to decribe the general picture of local tax revenues, regional retributions, and the results of separated regional wealth management (HPKDYD) and analyze the influence of each factor that effects regional original income (PAD), namely regional taxes, regional retributions, and management results regional wealth which is separated from the original regional income of the Regency and City of North Kalimantan Province in 2013-2020. The objects of this research are 4 districts (Malinau regency, Nunukan regency, Bulungan regency, Tana Tidung regency) and 1 city (Tarakan city). The method used is panel data regression analysis and classical assumption included multicollinearity test, heteroscedaticity test, autocorellation test, chow test, hausman test, T-test, F-test, and coefficient of determination. The results of this study indicate that the local tax variable and HPKDYD have a positive but not significant effect on local revenue. Meanwhile, the results of the regional retributions variable show that there is no positive and insignificant effect on local revenue.